Standard Chartered Bank and difference between SME loan of SCB and the City Bank Limited - Hoque, Md. Tayeenul (BRAC University, 2010)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2009.